The protein arginine deiminases: Structure, function, inhibition, and disease1. Issue 2 (22nd November 2012) - Bicker, Kevin L.; Thompson, Paul R.; Trievel, Ray
Abstract The post‐translational modification of histones has significant effects on overall chromatin function. One such modification is citrullination, which is catalyzed by the protein arginine deiminases (PADs), a unique family of enzymes that catalyzes the hydrolysis of peptidyl‐arginine to form peptidyl‐citrulline on histones, fibrinogen, and other biologically relevant proteins. Overexpression and/or increased PAD activity is observed in several diseases, including rheumatoid arthritis, Alzheimer's disease, multiple sclerosis, lupus, Parkinson's disease, and cancer. This review discusses the important structural and mechanistic characteristics of the PADs, as well as recent investigations into the role of the PADs in increasing disease severity in RA and colitis and the importance of PAD activity in mediating neutrophil extracellular trap formation through chromatin decondensation. Lastly, efforts to develop PAD inhibitors with excellent potency, selectivity and in vivo efficacy are discussed, highlighting the most promising inhibitors. © 2012 Wiley Periodicals, Inc. Biopolymers 99: 155–163, 2013.